Analisis Kesalahan Siswa dalam Menyelesaikan Soal Cerita pada Materi Pola Bilangan Kelas VIII di SMP Swasta Rangga Rame - Mbayu, Dominggus Wuru; Making, Samuel Rex M.; Lede, Yulius Keremata (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine students' mistakes in solving story problems on number pattern material in class VIII of Rangga Rame Private Junior High School for the 2023/2024 school year. The type of research used in this study is qualitative. The subjects in the study were students of class VIII Rangga Rame Private Junior High School with a total of 17 students. The object of this study is the analysis of student errors in solving story problems on number pattern material. Data collection techniques there are tests and interviews. Data analysis techniques go through three stages, namely data reduction, data presentation, and conclusions. The results of the data analysis showed that the overall percentage of students who made mistakes in solving story problems on the number pattern material reviewed from the Newman procedure at the problem reading stage was 0%, the problem understanding stage was 71%, the transformation stage was 92%, the process skills stage was 98%, and the answer writing stage was 98%.